Medical technology and illness experience of patients undergoing coronary artery bypass grafting surgery in contemporary Thai society - Kingkeaw Kwankhao (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The objective of this study was to study the subjective illness of patients who had undergone coronary artery bypass grafting surgery, in a social, economic and cultural context characterized by inequalities in the physician-patient relationship, medical service provision and health policy. Qualitative methodology was utilized. The data were collected at a central hospital in Eastern Thailand through narrative interviews with 7 participants. All were receiving medication to control cardiovascular disease and received a coronary artery bypass grafting surgery at the studied hospital or elsewhere, 6 months to 10 years ago. Cyborg Anthropology and Critical Medical Anthropology Perspectives were used to analyze medical technology on 4 levels: the individual, the relationship between the patient and medical personnel, the medical institution and national health policy. The 7 participants were socio-culturally diverse. Heart surgery patients are affected by the social structure, especially the state policies of public health insurance in an era of globalization and democratization by developing country to imitate west. While such policies attempt to cover all Thai citizens at considerable expense, improvements are still needed in terms of quality, the medical service provision, which focuses on the use of advance medical technology and currently operates on capitalist principles, and in the patient-physician relationships, in which physicians currently play the role of peddlers of medical technology to patients. The individual heart surgery experiences with medical technology saves lives on one hand, but ends them or causes disability on the other. Patients awaiting heart surgery are in a vulnerable position, fending off death, and facing great uncertainty about their future. Patients gave their cultural and religious perspective amulets. Medical technology was seen as mysterious and beyond questioning about its effectiveness in curing illness. Medical technologies operate within transnational capitalism and thus provide one-sided information about the technology saves human lives. The participants who had undergone the heart surgery could be divided into 3 categories: who negotiate their situation of lives intertwined with medical technology, who were submissive toward the technology, and who opposed it. When medical technology became a part of human body, it reduced that person's humanity by causing endless dependence on itself. The use of medical technology for saving human lives should take cultural relativism perspective of holistic life with science and culture.